2007
DOI: 10.1016/j.juro.2006.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Testicular and Pituitary Inclusion Formation in Fragile X Associated Tremor/Ataxia Syndrome

Abstract: Fragile X associated tremor/ataxia syndrome inclusions are formed in tissues outside of the central nervous system. Involvement of the testicles and the pituitary gland may lead to neuroendocrine dysfunction, including testosterone deficiency. These noncentral nervous system components of fragile X associated tremor/ataxia syndrome require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 18 publications
5
79
1
Order By: Relevance
“…Elevated levels of FSH have been found to reflect decreasing ovarian reserve (MacNaughton et al, 1992), which can be correlated to the risk of developing POF seen in female PM carriers. Interestingly, intranuclear inclusions have been reported in the testicles of two men with FXTAS; inclusions were present in the anterior and posterior pituitary gland of one of these for whom the pituitary gland was available (Greco et al, 2007). Finally, a reduced amygdala response has been reported in PM male carriers which may explain the etiology of psychological symptoms involving emotion and social cognition as well ).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Elevated levels of FSH have been found to reflect decreasing ovarian reserve (MacNaughton et al, 1992), which can be correlated to the risk of developing POF seen in female PM carriers. Interestingly, intranuclear inclusions have been reported in the testicles of two men with FXTAS; inclusions were present in the anterior and posterior pituitary gland of one of these for whom the pituitary gland was available (Greco et al, 2007). Finally, a reduced amygdala response has been reported in PM male carriers which may explain the etiology of psychological symptoms involving emotion and social cognition as well ).…”
Section: Introductionmentioning
confidence: 96%
“…A link has been suggested between pituitary inclusions and dysregulated neuroendocrine function in patients with FXTAS. Increased Follicle Stimulating Hormone (FSH) (Hundscheid et al, 2001;Sullivan et al, 2005;Greco et al, 2007) and decreased inhibin A and B levels in female PM carriers were reported even in those who are cycling normally, suggestive of early ovarian aging and ovarian compromise (Welt et al, 2004). Elevated levels of FSH have been found to reflect decreasing ovarian reserve (MacNaughton et al, 1992), which can be correlated to the risk of developing POF seen in female PM carriers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kenneson et al (2001) [10] found that these patients have an increase in FMR1 RNA transcription proportionally related to the number of CGG repeats and a decrease in FMRP translation inversely related to the number of CGG repeats. The excess of FMR1 mRNA seen in carriers leads to dysregulation of several proteins and its deposition, along with FMR1 mRNA, in the form of cellular inclusions in several parts of the body including the central nervous system, peripheral nervous system (especially autonomic ganglia), Leydig cells, and pituitary among others [11][12][13]. Therefore, any pathology associated with FMR1 premutations would not be caused by a complete absence of FMRP like FXS is, but probably due to partial FMRP deficiency and/or RNA toxicity.…”
Section: Introductionmentioning
confidence: 99%